Historiography and Identity. (Turnhout, Belgium)
2. cilt (viii, 356 sayfa)
Keywords: “This second volume of the series studies the social function of historiography in the Justinianic age and the post-Roman kingdoms of the West. The papers explore how writers in Constantinople and in the various kingdoms from Italy to Britain adopted late antique historiographical traditions and adapted them in response to the new needs and challenges created by the transformation of the political and social order. What was the significance of their choices between different models (or their creation of new ones) for their ‘vision of community’? The volume provides a representative analysis of the historiographical resources of ethnic, political, and religious identifications created in the various Western kingdoms. In doing so, it seeks to understand the extant works as part of a once much wider and more polyphonic historiographical debate.” --